Effects of sowing dates and weed management on productivity of irrigated wheat (Triticum aestivum) - SHARMA, NEETU; KUMAR, ANIL; SHARMA, B C; CHAND, LEKH; SHARMA, VIKAS; KUMAR, MANISH (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during rabi 2012–13 and 2013–14 at research farm of SKUAST-Jammu to study the effect of sowing dates and weed management practices on productivity of wheat (Triticum aestivum L.). Among sowing dates, 15th November sown crop recorded lowest total weed density and total dry weight of weeds as compared to crop sown on 25th December. Crop sown on 15th November also recorded highest yield attributes and grain yield which ultimately led to maximum net returns of ₹51316/ha and B:C ratio (1.06). Significantly low weed density and dry matter of weeds and higher grain yield were recorded with ready mix application of sulfosulfuron + metsulfuron 30 g/ha + 2 g/ha. Maximum weed control efficiency, crop resistance index and lowest weed index, weed persistence index were observed with the application of sulfosulfuron + metsulfuron 30 g/ha + 2 g/ha. Significantly highest sedimentation value, crude protein and glutenin content was also recorded with the ready mix application of sulfosulfuron + metsulfuron 30 g/ha + 2 g/ha as post emergence. Maximum benefit:cost ratio was also obtained with the application of sulfosulfuron + metsulfuron 30 g/ha + 2 g/ha